Neurological complications and pathogenetic therapy for chronic nitrous oxide intoxication (“laughing gas”) in nightclub visitors - N. А. Suponeva; D. А. Grishina; D. А. Grozova; N. V. Belova; М. А. Ginzberg; А. S. Rizvanova; М. А. Piradov (Нервно-мышечные болезни)
Background. Nitrous oxide abuse (“laughing gas”, N2O) is common among young people attending nightclubs. Contrary to popular belief about the safety of N2O, in some cases neurological complications develop due to a deficiency of vitamin B12, the activity of which is blocked by N2O. Purpose of the study – to determine the typology and course of neurological disorders in a group of patients who regularly use “laughing gas”. To note the key diagnostic markers that allow verification of vitamin B12 deficiency induced by nitrous oxide consumption. To describe pathogenetic therapy features and follow-up. Materials and methods. The study included 12 patients (10 men and 2 women) aged 18 to 45 years (average age 29 years) with a diagnosis of B12-deficient myelopolyneuropathy induced by regular use of nitrous oxide. Results. The most common neurological complication of nitrous oxide abuse for more than 1 month was a generalized lesion of the peripheral nerves with acute or subacute distal symmetric sensory or sensorimotor axonal polyneuropathy. In the clinical picture, sensory complaints and disorders prevailed. Paresis developed in half of the cases. A typical neuroimaging symptom characteristic of funicular myelosis was rarely detected (16.7 %). A decrease in B12 vitamin level could most reliably be diagnosed only indirectly, by the presence of hyperhomocysteinemia (91.7 % of cases). In all cases that were followed-up, prolonged therapy with cyanocobalamin led to partial (n = 5; 62.5 %) or complete (n = 3; 37.5 %) regression of neurological symptoms. Conclusion. Caution regarding the use of nitrous oxide should be in all cases of predominantly sensory polyneuropathy with acute or subacute development in young and middle-aged people. A thorough history taking (targeted survey on the fact of nitrous oxide consumption) and diagnostics (testing the level of homocysteine, if possible methylmalonic acid) allow you to not miss a deficiency of vitamin B12, the treatment of the consequences of which with timely verification and adequate correction is quite effective. It is recommended that the level of homocysteine in the blood to be regularly monitored during the treatment (in order to achieve its normalization).